Mediating Role of Attitude Toward Green Brands in Green Purchase Intention - Geralvine, Edgar; Tanuwijaya, Haryanto; Supriyanto, Antok (Electronic Journal of Education, Social Economics and Technology, 2025)
This study is to examine among environmentally concerned customers in Mojokerto the impact of Green Brand Positioning, Green Brand Knowledge, Green Perceived Value, and Attitude Towards Purchasing Green items on Purchase Intention of Maybelline Green Edition cosmetic items. Following non-probability with judgemental sampling, then random sampling produced a sample of 170 responders. Direct messaging to green customers and online questionnaires sent on social media such Facebook, Twitter, and Instagram helped to gather data as well. Structural Equation Modelling (SEM) was used with SmartPLS 4 program to data analysis. The study shows that, both directly and by mediation, Green Brand Positioning, Green Brand Knowledge, and Green Perceived Value significantly influence Purchase Intention. Furthermore found to have a major impact on purchase intention of green items is attitude towards buying them.